Measurement of neutral current cross sections at high Bjorken-x with the ZEUS detector at HERA - Cooper-Sarkar, A; Devenish, R; Foster, B; Gwenlan, C; Walczak, R; ZEUS Collaboration (316 others) (Springer, 2006)
A new method is employed to measure the neutral current cross section up to Bjorken-x values of one with the ZEUS detector at HERA using an integrated luminosity of 65.1 pb-1 for e+p collisions and 16.7 pb-1 for e-p collisions at s√=318GeV and 38.6 pb-1 for e+p collisions at s√=300GeV. Cross sections have been extracted for Q2≥648 GeV2 and are compared to predictions using different parton density functions. For the highest x bins, the data have a tendency to lie above the expectations using recent parton density function parametrizations.